Penyuluhan Teknik Deep Cleaning Sepatu Secara Mandiri Untuk Pemeliharaan Kualitas dan Keawetan Sepatu Kepada Para Pemuda Karang Taruna Desa Mojowiryo Kecamatan Kemlagi Kabupaten Mojokerto - Sugeng Eko Yuli Waluyo; Adelia Rochmawati; Mukhammad Nizar Sidiq; Achmad Misbachul Munir; Salsaliya Eka Faizha; Imro’atus Tsaniyah; Fahri Wardana Wijaya; Erlina Nuzulul Fitria; Viona Safira Herlanda; Vinetta Ashya Sodikin; Mahardika Moksa Hakiki; Layly Yuly Dwi Masithoh; Andrian Kusuma Maulana; Muhammad Wahyu Efendi; Syaiful Hudib; Elda Noveria; Atha Karunia Gemilang; Alfin Budiono; Dhitha Arum Sufi Yana; Rachma Yulia; Devina Zaniyatul Firdaus; Nanda Rahma Nur Aisyah; Ayu Made Ray Diva Adinata (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
Community Service Lecture (KKN) is a program held by the campus to serve the community by students with the aim of helping the local community to solve problems in the village. The socialization activities were carried out in Mojowiryo village, Kemlagi sub-district. The activity aims to foster a sense of enthusiasm for cleaning small things, especially taking care of shoes. This socialization is also intended for young people to open business opportunities to reduce unemployment in the village with a shoe laundry business. In the implementation of these activities carried out by means of questions and answers and presentations by the KKN team. The results obtained from these activities are that the community can find out how to take care of their shoes properly and correctly with makeshift tools to make a profitable business field.